Water remains a blind spot in climate change policies - Douville, H.; Allan, R. P.; Arias, P. A.; Betts, R.A.; Caretta, M. A.; Cherchi, A.; Mukherji, Aditi; Raghavan, K.; Renwick, J. (2022)
For the first time in the latest Assessment Report of the Intergovernmental Panel on Climate Change (IPCC), water has been the focus of dedicated chapters in both Working Group 1 (Chapter 8) and 2 (Chapter 4). Nevertheless, we argue here that water has not yet received the full attention it deserves from both scientists and policymakers for several reasons. Firstly, the historical focus on temperature change has been further increased with the use of global warming levels motivated by an aim to be consistent with current policy framings. Secondly, an increasing attention paid to extreme weather has sometimes overshadowed longer time-scale changes such as the aridification of an increasing fraction of arable land and the increasing variability of the water cycle from month to month, season to season, and year to year that also yield cascading impacts on all water use sectors. Thirdly, a stronger focus is needed on understanding the effectiveness of current and future adaptation strategies in reducing water-related climate risks. Finally, the role of water has not been adequately recognized in the assessment of mitigation strategies although the compliance with the Paris Agreement and the current pledges all require a massive deployment of land based strategies whose feasibility and efficiency heavily depend on water resources. It is thus essential to develop a more integrated approach to water and climate change, that would allow scientists and policymakers to “close the loop” between mitigation options, water cycle changes, hydrological impacts and adaptation.